The Effectiveness of Instructional Video Media in Coffee Knowledge Courses (Baristas) - Rais, Syafruddin; Verawardina, Unung; Ambiyar, Ambiyar; Wakhinuddin, Wakhinuddin; Ramadhani, Dochi (Jurnal Pendidikan Indonesia, 2020)
This study aims to determine the effectiveness of the use of instructional video media in coffee knowledge course (barista). In design, this was a quasi-experimental study that implemented learning methods in experimental class and control class. The sample in this study was students taking the coffee knowledge course, consisting of 22 students in the experimental class and 22 students in the control class. Instruments used were learning outcome test and learning activity sheet. The findings showed that video media learning resulted in good learning outcomes, while conventional learning resulted in fair learning outcomes. In terms of activity, students who learnt using video media were more active that those who learnt in conventional setting. It was concluded that the learning outcomes and activity of students in the experimental class were better than those in control class, in other words, instructional video media was more effective than conventional learning for the coffee knowledge course. The novelty observed was compared to conventional learning and it showed that videos containing elements of texts, images, illustrations led instructors or lecturers to teach in a more practical way that facilitated material understanding, unlike conventional learning in which media were rarely used.